Registered mental nurses' experiences of nurse-patient relationships in acute care. - Ian Taylor (2012)
The changing context of mental health care provision in the United Kingdom in the last three decades has seen significant change in acute inpatient services. Service users have expressed dissatisfaction about current service provision and care. Nurses continue to represent the largest professional group providing care in these services. Comparatively little is known from nurses' perspectives about the present nature of the nurse-patient relationship in acute mental health inpatient settings. The purpose of this research study was to explore with a sample of 14 registered mental nurses, their experiences about the nature of the nurse-patient relationship. An interpretive, phenomenological approach was adopted. The principal research question asked 'What are registered mental nurses' experiences of the nature of the nurse-patient relationship in working age acute inpatient mental health care settings?' Following ethical approval, unstructured, individual interviews were used as the primary method of data collection. Transcribed interview texts were analysed hermeneutically, supplemented with the researcher's field notes and reflective journal. Key findings included the impact of poor ward environments, increased patients' acuity of illness, and multiple, competing demands placed on nursing time. Although nurses valued human interpersonal relationships with patients, they struggled to achieve their aspirations for the nurse-patient relationship, owing to a range of factors including organisational constraints, inexperience, and limited post-registration professional development. Nurses could experience stress and emotional fatigue, and their needs for support were not always met. These factors may challenge possibilities for the development of therapeutic nurse-patient relationships. Whilst nurses appear to acknowledge the benefits of therapeutic nurse-patient relationships, they may be insufficiently prepared to achieve their ideals, given the challenges of working within an area of practice which provides for short term admissions focussed on acute risk management and containment.